AN ANALYSIS, RESEARCH AND UNTIING OF COMPETITIVE TASKS, IS DURING STUDENT'S OLYMPIAD FROM INFORMATICS - Zhukovskiy, C.C. (Journal of Information Technologies in Education (ITE), 2010)
The method of preparation of students is offered to the decision of olympiad tasks on an informatics. Resulted technology of analysis of task and its condition, construction of mathematical model, realization of algorithm, by a programming and testing of program-decision language. Strategy of conduct of student is offered during a competition.